Estimating the effects of Light Rail Transit (LRT) system on the property values in the Klang Valley, Malaysia a hedonic house price approach - Dziauddin Mohd Faris, Alvanides Seraphim, Powe Neil (N/A, 2013)
Estimating the effects of Light Rail Transit (LRT) system on the property values in the Klang Valley, Malaysia a hedonic house price approach by Dziauddin Mohd Faris, Alvanides Seraphim, Powe Neil,